STRUCTURAL CLASSES OF VERBS IN ENGLISH AND UZBEK - Mansurova , Oysara; Bafoyeva, Nilufar ("Science Shine" International scientific journal, 2024)
Annotation: This comparative study delves into the structural classes of verbs in English and Uzbek, exploring their morphological, syntactic, and semantic dimensions. In English, verbs span diverse categories including transitive, intransitive, copular, auxiliary, modal, and phrasal verbs, each embodying distinct syntactic and semantic functions. Conversely, Uzbek verbs manifest as transitive, intransitive, reflexive, and causative, reflecting typological nuances within the Turkic language family. Morphologically, both languages employ various strategies for encoding tense, aspect, mood, person, and number. Syntactically, English and Uzbek verbs exhibit divergent word order patterns and auxiliary usage. Semantically, verbs in both languages convey rich layers of meaning, encapsulating actions, states, and modality. This comparative analysis sheds light on linguistic typology, facilitating insights into cross-linguistic variation and the implications for language pedagogy, translation studies, and linguistic research.